Study to estimate the prevalence of thyroid disorders in pregnant women of North Gujarat region of India - Purohit, Niravkumar H.; Pathan, Rashidkhan B.; Choudhary, Prema Ram (International Journal of Advances in Medicine, 2022)
Background: The thyroid function is changed during early stage of pregnancy. Various thyroid disorders throughout pregnancy are related with grave maternal and fetal outcomes. The geographical variation in the prevalence of hypothyroidism during pregnancy is very wide and generally assessed for thyroid disorders are recommended in the pregnancy. Therefore, present study aimed to estimate the prevalence of thyroid disorders in pregnant women of North Gujarat, India. Methods:The present cross-sectional study was done on 200 pregnant women in the department of general medicine at Banas medical college and our trust-based hospital in North Gujarat, India, over a period of one year from July 2020 to June 2021. The patients’ demographic profile was recorded; detailed history and meticulous examination were performed in the entire cases. Serum thyroid-stimulating hormone (TSH), T3 (triiodothyronine) and T4 (thyroxine) were analyzed. Results: The overall prevalence of various thyroid disorders 13%. The most frequent thyroid disorder reported was subclinical hypothyroidism encompassing of 8%, followed by overt hypothyroidism 3% in women and the prevalence of subclinical hyperthyroidism was 2% which was least in our study. Conclusions:In our study, we conclude that subclinical hypothyroidism is more common than hyperthyroidism in pregnant women. Therefore, we suggested that thyroid function tests should be include along with other routine investigations during pregnancy to identify thyroid dysfunction and minimize the feto-maternal complications during pregnancy and after birth.